Augmented Reality for Event Promotion - Tiago Lameirão; Miguel Melo; Filipe Pinto (Computers)
This article presents the development of an augmented reality (AR) application aimed at promoting events in urban environments. The main goal of the project was to create an immersive experience that enhances user interaction with their surroundings, leveraging AR technology. The application was built using Django Rest Framework (DRF) for backend services and Unity for the AR functionalities and frontend. Key features include user registration and authentication, event viewing, interaction with virtual characters, and feedback on attended events, providing an engaging platform to promote urban events. The development process involved several stages, from requirements analysis and system architecture design to implementation and testing. A series of tests were performed, confirming that the application meets its objectives. These tests highlighted the system’s ability to enhance user interaction with urban environments and demonstrated its potential for commercialization. The results suggest that the AR application contributes to innovation in smart cities, offering a new avenue for promoting events and engaging local communities. Future work will focus on refining the user experience and expanding the app’s functionality to support more complex event scenarios.